2017
DOI: 10.1111/jcmm.13289
|View full text |Cite
|
Sign up to set email alerts
|

Changes in haematopoietic progenitor colony differentiation and proliferation and the production of different abzymes in EAE mice treated with DNA

Abstract: Immunization of experimental autoimmune encephalomyelitis (EAE)‐prone C57BL/6 mice with MOG 35‐55 (a model used to study aspects of human multiple sclerosis) is known to lead to the production of various abzymes. The production of catalytic IgGs that can efficiently hydrolyse myelin basic protein (MBP), MOG and DNA is associated with changes in the profile of differentiation and level of proliferation of mice bone marrow haematopoietic stem cells (HSCs). As MOG simulates the production of abzymes with high DNa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
344
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 27 publications
(350 citation statements)
references
References 37 publications
6
344
0
Order By: Relevance
“…There are several different EAE models, each mimicking a specific facet of MS (for review see). C57BL/6 mice were recently used to study possible mechanisms of spontaneous, myelin oligodendrocyte glycoprotein (MOG)‐ and DNA‐accelerated development of EAE . We confirmed that immunization with MOG and DNA led to an acceleration of EAE development but was associated with various changes in HSC differentiation profiles, lymphocyte proliferation and apoptosis in different organs of mice.…”
Section: Introductionsupporting
confidence: 56%
See 4 more Smart Citations
“…There are several different EAE models, each mimicking a specific facet of MS (for review see). C57BL/6 mice were recently used to study possible mechanisms of spontaneous, myelin oligodendrocyte glycoprotein (MOG)‐ and DNA‐accelerated development of EAE . We confirmed that immunization with MOG and DNA led to an acceleration of EAE development but was associated with various changes in HSC differentiation profiles, lymphocyte proliferation and apoptosis in different organs of mice.…”
Section: Introductionsupporting
confidence: 56%
“…Immunization of mice with MOG and Pertussis toxin, and immunization with DNA without toxin was carried out as described in previously published protocol . The relative weight of mice and proteinuria (relative concentration of total protein in the urine, mg/mL) was analysed as before . Protein concentration in urine was measured using the Bradford assay with a bovine serum albumin standard.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations